Analisis restukturisasi usaha koperasi dalam upaya mempertahankan keberlangsungan usaha - Sukmahadi, Sukmahadi; Askariyah , Nova Ariyanti Qonita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
KKB UKOPIN is a primary cooperative located in the Sumedang Regency area. There are nine business units that are run which are included in the real sector and services, where four of these nine units experience losses. Ups and downs in running a business will still exist, so the health of the cooperative is very important to note so that the cooperative does not experience ongoing financial difficulties that will later experience bankruptcy. This study aims to analyze the restructuring of cooperative businesses to maintain business continuity in bankruptcy. This study uses the Altman Z-Score method to assess the level of cooperative bankruptcy. The results of the analysis obtained will be used to determine the business restructuring efforts carried out by the UKOPIN KKB management to be able to maintain and develop their business. The types of data used are primary and secondary data. In this research, the data analysis method used is the descriptive analysis method. The results of this study: the authors obtained the results of the assessment using the Altman Z-Score KKB UKOPIN method for the last five years, being in a safe zone, but cooperatives must make improvement efforts through actions that cover all aspects to maintain cooperative businesses.